Eosinophilic and lymphoplasmacytic enteritis in a horse - case report - Machado, R.C. [UNESP]; Teixeira, C.F.; Carvalho, H.D. (FapUNIFESP (SciELO), 2025)
ABSTRACT Among the Inflammatory Bowel Diseases in horses, eosinophilic and lymphoplasmacytic enteritis is rare and is characterized by an infiltrate of inflammatory cells, causing problems with nutrient absorption, diffuse neoformation and changes in the histological structure of all the tissue layers of the intestine. This report describes a case of eosinophilic and lymphoplasmacytic colitis in an 11-year-old male horse with progressive weight loss, sings of colic syndrome and apathy. No alterations were found in the blood Count, except for leukocytosis with neutrophilia. The biochemical examination showed an increase in indirect bilirubin, and the peritoneal fluid showed a high concentration of total protein, lactate and total nucleated cells. Ultrasound identified free fluid in the abdominal cavity and neoformation in the colon. In view of the findings, exploratory celiotomy was recommended; however, euthanasia was chosen considering the cost-benefit and zootechnical value of the animal. Post-mortem histopathological examination of fragments of the greater and lesser colon identified Lymphoplasmacytic colitis and eosinophilic colitis, chronic process, with no determined cause and treatment that is not always effective, but preventive health management measures minimize the triggering factors. RESUMO Dentre as doenças inflamatórias intestinais nos equinos, a enterite eosinofílica e linfoplasmocitária é rara, e caracterizada por um infiltrado de células inflamatórias, gerando problemas na absorção de nutrientes, neoformação difusa e mudança de estrutura histológica em todas as camadas teciduais do intestino. Este relato descreve um caso de colite eosinofílica e linfoplasmocitária em um equino macho, de 11 anos de idade, com emagrecimento progressivo, sinais de síndrome cólica e apatia. No histórico do animal, foi relatado emagrecimento progressivo e apatia. No hemograma, não foram encontradas alterações, exceto leucocitose com neutrofilia. No exame bioquímico, a bilirrubina indireta foi aumentada, e o líquido peritoneal apresentou elevada concentração de proteína total, lactato e células nucleadas totais. O exame ultrassonográfico identificou líquido livre na cavidade abdominal e neoformação no cólon. Em vista dos achados, recomendou-se a celiotomia exploratória; contudo, optou-se pela eutanásia, considerando-se o custo-benefício e o valor zootécnico do animal. O exame histopatológico post mortem de fragmentos do cólon maior e menor identificou colite linfoplasmocitária e colite eosinafilica, processos crônicos, sem causa determinada, cujo tratamento nem sempre é eficaz, mas com medidas preventivas de manejo sanitário, minimizam os fatores desencadeantes.